State features of research area of problem of provision of economic security of innovative project-oriented enterprises - Россошанська, Ольга Валентинівна (Technology audit and production reserves, 2013)
Identification of features of the modern state of research area of the problem of economic security of innovation project-oriented enterprises is based on the analysis of publications in the professional edition «International Journal of Business Innovation and Research» over the past five years. The analysis refers to the most extensive metrics of the model of scientific research developed by the authors - the research area. The tendency of transition from closed to open innovations was determined. It implies the need for a new approach to economic security - security of openness, not of protection. For proper organization of such activities, innovations should be understood as an open system, and the size of means needed to be invested in research and development should be compared with similar expenditures of competitors. For Ukrainian enterprises moving strategically towards the innovative project-oriented enterprises, in terms of its economic security it is necessary to form technological capacities of the whole enterprise and of each employee.